Prosedur Teori Konseling Psikoanalisis Dengan Memperhatikan Peran Dan Fungsi Konselor Dalam Hubungan Konselor Dan Konseling - Laura Maulita Agustin; Syafa’atun Nur Fajariyah; Pribadi Wahyu Santiko; Bakharudin All Habsy (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Psychoanalysis is a type of counseling that aims to release pent-up or deeply repressed emotions and memories or to lead the counselee to healing. In other words, the goal of psychoanalysis is to bring what is in the unconscious or subconscious to the level of consciousness. The writing in this article uses the literature study method. Literature study is a method of tracing and reviewing and understanding previously written sources from the last 10 years. The results of the research include several findings in the psychoanalytic theoretical approach such as (1) the purpose of psychoanalytic counseling, (2) the role and function of the counselor, (3) the experience of the counselee in counseling as well as the relationship between the counselor and the counselee and the limitations that exist in psychoanalytic counseling. (4) psychoanalytic counseling procedures There are also several stages in psychoanalytic theory, such as: (1) Assessment stage, (2) Development of transference, and (3) Working through transference.